Consumer Purchasing Behavior Analysis on Impulse Buying - I.G.A Prita Dewi Maharani; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACT               Retail business actors are required to be able to keep up with the times that aim to innovate in the field of product availability, know customer needs, services provided and also see the behavior of current consumers. Currently there are many modern shopping places in the urban community, namely lisfestyle center. In accordance with the formulation of the problem proposed, the purpose of this research is to find out Hedonic Shopping Motivation, Visual Merchandising, positive emotion, price discount affect Impulse Buying at Mall Bali Galeria.               In this study using quantitative methods. The number of samples used was 120 people determined by purposive sampling. Hypothesis testing is carried out with Structural Equation Modeling. Data collection techniques using research instruments in the form of questionnaires / questionnaires and analysis of the data used is quantitative / statistical with the aim to test the hypothesis that has been set.               The results showed that Hedonic Shopping Motivation had no significant effect on Impulse Buying. Hedonic Shopping Motivation has a positive and significant effect on positive emotion. The higher the consumer shopping motivation, the higher the emotional positive consumers will be the opposite. Visual Merchandising has a positive and significant effect on Positive Emotion. The higher visual consumer merchandising, the higher the positive emotion of consumers is the opposite. Visual Merchandising has no significant effect on Impulse Buying. Positive Emotion has a positive and significant effect on Impulse Buying. The higher the positive emotional consumers, the higher the impulse buying of consumers is the opposite. Shopping Lifestyle has a positive and significant effect on Impulse Buying. The higher the shopping lifestyle of consumers, the higher the impulse buying of consumers is the opposite. Hedonic Shopping Motivation has a positive and significant effect on Lifestyle Shopping. The higher the consumer shopping motivation, the higher the consumer shopping lifestyle is the opposite. Price Discount has a positive and significant effect on Impulse Buying. The higher the consumer's Discount Price, the higher the consumer's impulse buying is the opposite.               The conclusion from the study that Hedonic Shopping Motivation and visual merchandising do not significantly influence Impulse buying but through positive emotion as a moderating variable. This shows that a person's hedonism does not directly affect his desire to shop impulsively, but is also influenced by his positive emotional nature, so that hedonic shopping motivation and visual merchandising affect impulse buying through positive emotion. But the price discount can have a significant effect on impulse buying.                The findings of the research and analysis of this study can contribute to the development of knowledge in the field of management regarding consumer valuation of Hedonic Shopping Motivation, visual merchandising, positive emotion, shopping lifestyle, discount prices, Impulse Buying. Thus it is expected that further research can explore a matter or problem related to impulse buying. In addition, this research can also use different model specifications, explore new variables that have not been examined in this study, and can see phenomena that can influence the increase in impulsive purchases of consumers. Subsequent research can also be done in different places or by taking respondents and using different characteristics.